Pencabutan Kewarganegaraan Indonesia Anggota the Islamic State of Iraq and Syria (ISIS): di antara Kedaulatan Negara dan Hak Asasi Warga Negara - Diya Ul Akmal (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The growth of the Islamic State of Iraq and Syria (ISIS) has created complex issues for countries around the world. Radicalism awareness and propaganda's ability to spread are the issues. The downfall of ISIS was triggered with the death of its leader. ISIS militants from various nations, including Indonesia, were also impacted by this. Regarding the repatriation of Indonesian citizens and their citizenship status, there are both proponents and critics in the society. The aim of this research was to ascertain the citizenship status of Indonesian nationals who left their country and joined ISIS and to determine the legal standing of someone without a nationality. This is a qualitative study that employs the Normative Legal Method in conjunction with the Legislative Approach. The data was gathered from a literature review that included primary legal materials (statutory regulations), secondary legal materials (books and journals), and tertiary legal materials (Internet). The gathered data is analyzed and described in terms with scientific logic. The study revealed that many Indonesian nationals who joined ISIS desired to go back to their own country. Even yet, the Indonesian government has adopted a policy of revoking citizenship and refusing to repatriate Indonesian people who joined ISIS. The former Indonesian citizen is therefore stateless. The Indonesian government's policy is an assertion of state sovereignty and does not violate the human rights of former Indonesian citizen because the decision to leave Indonesia and join ISIS is totally personal to each former Indonesian citizen. The government needs to take more preventive actions through promoting Pancasila education and national values. This attempts to strengthen nationalism and prevent extremist ideas from spreading in Indonesia. In order to emphasize State Sovereignty more strongly in the development of the Indonesian state of law, security assurances and protection for the entire Indonesian population must also be improved.